A Highly Active Form of XCL1/Lymphotactin Functions as an Effective Adjuvant to Recruit Cross-Presenting Dendritic Cells for Induction of Effector and Memory CD8+ T Cells - Matsuo, Kazuhiko; Kitahata, Kosuke; Kawabata, Fumika; Kamei, Momo; Hara, Yuta; Takamura, Shiki; Oiso, Naoki; Kawada, Akira; Yoshie, Osamu; Nakayama, Takashi (Frontiers in Immunology, 2018)
The chemokine receptor XCR1 is known to be selectively expressed by cross-presenting dendritic cells (DCs), while its ligand XCL1/lymphotactin is mainly produced by activated CD8+ T cells and natural killer cells. Recent studies have shown that XCL1-antigen fusion proteins efficiently induce CD8+ T cell responses by preferentially delivering antigens to XCR1+ DCs. However, XCL1 per se was found to be a poor adjuvant for induction of CD8+ T cell responses. XCL1 is unique because of its lack of one of the two disulfide bonds commonly conserved in all other chemokines and thus has an unstable structure with a relatively weak chemokine activity. In the present study, we generated a variant form of murine XCL1 termed mXCL1-V21C/A59C that contained a second disulfide bond to stabilize its chemokine structure. We confirmed that mXCL1-V21C/A59C had much more potent chemotactic and calcium mobilization activities than the wild type XCL1 (mXCL1-WT). Intradermal injection of mXCL1-V21C/A59C, but not that of mXCL1-WT, significantly increased the accumulation of XCR1+CD103+ DCs in the injection site, and most of the accumulated XCR1+CD103+ DCs were found to take up co-injected ovalbumin (OVA). Furthermore, recruited XCR1+CD103+ DCs efficiently migrated to the draining lymph nodes and stayed for a prolonged period of time. Consequently, mXCL1-V21C/A59C strongly induced OVA-specific CD8+ T cells. The combination of OVA and mXCL1-V21C/A59C well protected mice from E.G7-OVA tumor growth in both prophylactic and therapeutic protocols. Finally, memory CTL responses were efficiently induced in mice immunized with OVA and mXCL1-V21C/A59C. Although intradermal injection of OVA and polyinosinic-polycytidylic acid (poly(I:C)) as an adjuvant also induced CD8+ T cell responses to OVA, poly (I:C) poorly recruited XCR1+CD103+ DCs in the injection site and failed to induce significant memory CTL responses to OVA. Collectively, our findings demonstrate that a highly active form of XCL1 is a promising vaccine adjuvant for cross-presenting DCs to induce antigen-specific effector and memory CD8+ T cells.